2018
DOI: 10.1016/j.bjm.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial and antimycobacterial activity and HPLC–DAD screening of phenolics from Chenopodium ambrosioides L.

Abstract: The main objective of this study was to demonstrate the antimicrobial potential of the crude extract and fractions of Chenopodium ambrosioides L., popularly known as Santa-Maria herb, against microorganisms of clinical interest by the microdilution technique, and also to show the chromatographic profile of the phenolic compounds in the species. The Phytochemical screening revealed the presence of cardiotonic, anthraquinone, alkaloids, tannins and flavonoids. The analysis by HPLC–DAD revealed the presence of ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
3
19
0
6
Order By: Relevance
“…Finally, the leaf extracts of Dysphania ambrosioide did not show any antibacterial activity against targets bacterial studied, as it was already demonstrated for Dysphania ambrosioide collected from Meknés city (Morocco) with no antibacterial effect [79] in contrary to Brazilian [80] or Pakisani [81] Dysphania ambrosioide which showed good antibacterial activity. These difference can be related to the geographical localization and environmental factors connected, who are one of the major determinants of plant secondary metabolites [82,83] responsible of the plant antimicrobial activity.…”
Section: B Discussionsupporting
confidence: 51%
“…Finally, the leaf extracts of Dysphania ambrosioide did not show any antibacterial activity against targets bacterial studied, as it was already demonstrated for Dysphania ambrosioide collected from Meknés city (Morocco) with no antibacterial effect [79] in contrary to Brazilian [80] or Pakisani [81] Dysphania ambrosioide which showed good antibacterial activity. These difference can be related to the geographical localization and environmental factors connected, who are one of the major determinants of plant secondary metabolites [82,83] responsible of the plant antimicrobial activity.…”
Section: B Discussionsupporting
confidence: 51%
“…Sousa et al (2012) could not detect antimicrobial activity from an ethanolic extract of the aerial parts up to 500 μ g/ml [ 55 ], as we did not observe it either for a methanolic extract from the leaves. Jesus et al (2017) determined for an ethanolic crude extract from leaves only very high MICs against Mycobacterium tuberculosis (1.25 mg/ml), E. faecalis (4.29 mg/ml), and P. aeruginosa (68.75 mg/ml) [ 56 ]. Generally, the whole aerial part is not considered (very) cytotoxic: Ruffa et al (2002) did not detect cytotoxic effects up to 1,000 μ g/ml for HepG2 [ 57 ], Koba et al (2009) found a CC 50 = 700 μ g/ml for HaCaT [ 50 ], and Barros et al (2013) determined CC 50 of 264 to 319 μ g/ml for HeLa, HepG2, and HCT-15 [ 58 ]; those values are in the range of CC 50 = 563 ± 66 μ g/ml ELM that we report for Caco-2.…”
Section: Discussionmentioning
confidence: 99%
“…Há relatos de seu uso na medicina popular para o tratamento de feridas, leucorreia, processos inflamatórios, como agente antihelmíntico e como anti-séptico oral . Estudos anteriores demonstraram seu potencial medicinal contra a ação de endoparasitas e fungos (Jesus et al, 2018), dentre estes, Development, v. 9, n. 7, e818974983, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4983 algumas espécies de Candida. Além disso, atividades ansiolíticas, curativas de feridas cutâneas, anti-inflamatórias (Trivellato Grassi et al, 2013;Penha et al, 2017) e atividades antioxidantes foram descritas.…”
Section: Discussionunclassified